KAJIAN KRITIS HUKUM PERTANAHAN DALAM PERSPEKTIF FIKIH - Nur, Iffatin (Ahkam: Jurnal Hukum Islam, 2014)
Conflicts of land had happened long time ago and commonly involved ulama to mediate the conflict. This fact led to the development of the science of Islamic law (Fikih). As a science, fikih is expected to provide theoretical basis for solving problems related to land ownership. Besides, it also provides theological basis to help solving problems of land from the perspective of religion. Kata kunci: Hukum Pertanahan, Fikih